2021
DOI: 10.3892/ijmm.2021.5002
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist targeting miR‑106b‑5p attenuates acute renal injury by regulating renal function, apoptosis and autophagy via the upregulation of TCF4

Abstract: Acute renal injury (ARI) is a life-threatening condition and a main contributor to end-stage renal disease, which is mainly caused by ischemia-reperfusion (I/R). miR-106b-5p is a kidney function-related miRNA; however, whether miR-106b-5p regulates the progression of ARI remains unclear. The present study thus aimed to examine the effects of miR-106b-5p antagonist on the regulation of ARI progression. It was found that miR-106b-5p expression was upregulated in the renal tissue of rats with I/R-induced ARI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…27 Besides, Antagonists targeting miR-106b-5p attenuate acute kidney injury by upregulating TCF4 to modulate renal function, apoptosis, and autophagy. 28 A recent study suggested that miR-106b-5p expression levels were significantly increased in macrophages undergoing ER stress due to vitamin D deficiency, 29 which is highly in accordance with our findings. Despite a certain amount of evidence presented by these studies, it was not explored how the regulatory relationship between miR-106b-5p and ER stress was precisely controlled.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27 Besides, Antagonists targeting miR-106b-5p attenuate acute kidney injury by upregulating TCF4 to modulate renal function, apoptosis, and autophagy. 28 A recent study suggested that miR-106b-5p expression levels were significantly increased in macrophages undergoing ER stress due to vitamin D deficiency, 29 which is highly in accordance with our findings. Despite a certain amount of evidence presented by these studies, it was not explored how the regulatory relationship between miR-106b-5p and ER stress was precisely controlled.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, inhibition of miR‐106b‐5p expression significantly ameliorated the progression in lipopolysaccharide (LPS)‐induced AKI 27 . Besides, Antagonists targeting miR‐106b‐5p attenuate acute kidney injury by upregulating TCF4 to modulate renal function, apoptosis, and autophagy 28 . A recent study suggested that miR‐106b‐5p expression levels were significantly increased in macrophages undergoing ER stress due to vitamin D deficiency, 29 which is highly in accordance with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The upregulation of miR-106b in rat kidneys subjected to ischemia/reperfusion injury reduced cell proliferation and promoted apoptosis and autophagy by targeting transcription factor 4 (TCF4) [ 100 ]. Macrophage-derived miR-106b was recently associated with inflammation-induced hypertension in mice [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EA treatment of SCIs in rats induces changes to miRNA expression profiles, as also demonstrated in previous studies [ 34 ]. MiR-106b-5p, a member of the 106b-25 cluster and a paralogue of the 17–92 cluster [ 35 ], has been well-studied in many diseases, including breast cance [ 35 ], and acute renal injury [ 36 ]. Recently, miR-106b-5p was found to be abnormally expressed in the spinal cords of mice models of neuropathic pain [ 4 ].…”
Section: Discussionmentioning
confidence: 99%